La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Ce mémoire a pour but d'examiner l'éventuel impact qu'a eu la quatrième vague du féminisme sur la situation des femmes dans le champ littéraire. Dans sa première partie de contextualisation, il trace les contours d'une histoire littéraire au féminin marquée par l'invisibilisation, l'exclusion et la marginalisation. Dans sa seconde partie, il fait état d'une série de transformations ayant récemment agité le monde de l'édition depuis la déferlante #MeToo, la plus notable étant l'essor inédit pris par l'édition d'ouvrages de non-fiction féministes, une pratique qui témoigne tantôt de l'engagement profond d'une série de nouvelles maisons d'édition indépendantes, tantôt de la pratique du "feminism washing" par les grandes maisons généralistes. La troisième et ultime partie vise à répondre à la question suivante : les inégalités de genre, de quelque nature qu'elles soient, affectent-elles autant le champ littéraire depuis #MeToo? Y seront abordées les questions du plafond de verre, des inégalités salariales, du capital symbolique accordé aux autrices et du harcèlement sexuel au sein du milieu littéraire.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; discipline; intersectionnalité; inégalités; metoo; mémoires/thèses; patriarcat; prix littéraires; périodes historiques; ressource en ligne; sciences humaines; sociologie; sofia; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles; écriture des femmes*; études littéraires

Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
https://doi.org/10.13016/M2QR4NT6S
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques